Simulation and Experiment Study of Chain Aggregate Structure in Magnetic Fluid. Issue 201 (2nd September 2019) - Ying, Yu; Xu, Ke; Si, Guang-Yuan; Zhao, Ji-Zhong
Abstract: Magnetic fluid is a novel magnetic functional material. The magneto-optical properties are displayed due to the tunability. In the paper, the material characterization was studied theoretically and experimentally. In the simulation, a rod-like magnetic nanoparticle model was used to simulate the motion of the magnetic particles. In the experiment, an experimental setup was designed to observe the change of the microstructure. The results showed that the magnetic particles can be aggregated to form several magnetic chains when the applied magnetic field exceeded 100 Oe. The novel magneto-optical device exhibits advantages of low cost, small size, and easy formation.